2012
DOI: 10.1016/j.bbamem.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interactions of two arginine-rich peptides with different cell internalization capacities

Abstract: Cell penetrating peptides (CPPs) can cross cell membranes in a receptor independent manner and transport cargo molecules inside cells. These peptides can internalize through two independent routes: energy dependent endocytosis and energy independent translocation across the membrane, but the exact mechanisms are still unknown. The interaction of the CPP with different membrane components is certainly a preliminary key point that triggers internalization, such as the interaction with lipids to lead to the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
77
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 39 publications
7
77
0
1
Order By: Relevance
“…Green 3]. 48 They found that the Tat protein from HIV-1 was internalized into 49 cells and Vives et al, found in 1997 the minimal sequence that was 50 responsible for the protein internalization [4]. Following this finding, 51 penetratin was discovered in 1994 by the group of Alain Prochiantz 52 [5].…”
mentioning
confidence: 96%
“…Green 3]. 48 They found that the Tat protein from HIV-1 was internalized into 49 cells and Vives et al, found in 1997 the minimal sequence that was 50 responsible for the protein internalization [4]. Following this finding, 51 penetratin was discovered in 1994 by the group of Alain Prochiantz 52 [5].…”
mentioning
confidence: 96%
“…290ability to bury deeper in lipid bilayers however would not imply better 291 translocation of a peptide[23,24]. Indeed peptides with higher 292 hydrophobicity might have weaker penetrating ability since peptides 293 interact more strongly with the lipid core of the liposome[25].…”
mentioning
confidence: 98%
“…At 23 their minimal inhibitory concentrations (MICs), these peptides completely killed cells of multidrug-resistant, 24 enterohemorrhagic pathogen Escherichia coli O157:H7 within 1-5 min. In addition, both peptides exhibited 25 anti-biofilm activity at sub-MIC levels.…”
mentioning
confidence: 99%
“…1B) is in agreement with the results of other researchers demonstrating that a deep polymer insertion into the bilayer is not always required for membrane destabilization. 30 When increasing the cholesterol proportion in the liposomal formulation, the enhancement of membrane rigidity and elasticity as well as the adsorption of polymer on the liposomal surface lead to a lower leakage at pH 7.4. …”
Section: Effect Of Cholesterolmentioning
confidence: 99%